Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Produktivitas Kerja Melalui Komitmen Organisasi Sebagai Variabel Intervening pada PT. Sumber Karya Indah Bogor - Helda Pebrasari; Palahudin Palahudin; Titiek Tjahja Andari (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the influence of organizational culture and job satisfaction variables on work productivity through organizational commitment at PT Sumber Karya Indah Bogor. The research design employs descriptive and verification methods with a quantitative approach. The population of this study includes 53 employees of PT Sumber Karya Indah Bogor, all of whom were taken as the sample using a non-probability sampling technique, specifically saturated sampling. The data analysis method used is Path Analysis, including t-tests and Sobel tests for the mediating variable, with IBM SPSS 25.00 software. The results show that organizational culture and job satisfaction have a direct, positive, and significant influence on organizational commitment. Furthermore, both organizational culture and job satisfaction have a direct, positive, and significant effect on work productivity. Organizational commitment also directly, positively, and significantly influences work productivity and serves as a mediating variable between organizational culture and job satisfaction and work productivity.